Lacto-fermented garlic sauce improved the quality and extended the shelf life of lamb meat under the chilled condition - Azhari, Siti Hajar; Daud, Nuraldayana; Muhialdin, Belal J.; Joghee, Naadjidah; Kadum, Hana; Meor Hussin, Anis Shobirin (Elsevier, 2023)
This study evaluated the potential of fermented garlic as a marinated lamb sauce ingredient to improve the quality and shelf life of chilled lamb. Garlic was subjected to Lacto-fermentation for 72 h at 37 °C using Lacticaseibacillus casei. The 1H NMR metabolomics profile showed the presence of eight amino acids and five organic acids in fermented garlic, indicating the attribution to the antioxidant and antimicrobial activities. The FRAP and DPPH assays of fermented garlic revealed antioxidant activities of 0.45 ± 0.09 mmol/100 g DW and 93.85 ± 0.02 %, respectively. Meanwhile, fermented garlic inhibited the growth of Escherichia coli (95 %), Staphylococcus aureus (99 %) and Salmonella Typhimurium (98 %). When fermented garlic was added to the marinade sauce, it successfully reduced the microbial load of lamb meat by 0.5 log CFU/g after 3 days of storage. There were no significant differences in color between the control and marinated lamb after 3 days of marinating in a sauce formulated with fermented garlic. Furthermore, marinated lamb significantly improved water-holding capacity, texture, juiciness, and overall acceptance. These findings indicated a potential addition of fermented garlic in marinade lamb sauce recipes to improve the quality and safety of meat products.